Theatre Inauguration Ceremony and Symbolic Representation - BARTHA, Katalin Ágnes (Studia Universitatis Babeș-Bolyai Dramatica, 2017)
The inauguration of the theatre building in Farkas street can be considered as a landmark of the Hungarian theatre history of Transylvania. The ceremony from 1821 has become a canonical event of Hungarian acting. The study analyzes first how the National Hungarian Theatre was constituted in the frame of the inauguration ceremony referring also to the symbolics of it as a visual and event-like frame of theatre historical remembrance. Then, will focus on two anniversary celebrations (from 1871 and 1892), in order to analyze how various elements of the anniversary celebrations relate to each other in the context of the institutionalization process.